Modulation of phospho-proteins by interferon-alpha and valproic acid in acute myeloid leukemia - Forthun, Rakel Brendsdal (J Cancer Res Clin Oncol, 2019)
PURPOSE: Valproic acid (VPA) is suggested to be therapeutically beneficial in combination with interferon-alpha (IFNα) in various cancers. Therefore, we examined IFNα and VPA alone and in combinations in selected AML models, examining immune regulators and intracellular signaling mechanisms involved in phospho-proteomics. METHODS: The anti-leukemic effects of IFNα and VPA were examined in vitro and in vivo. We mapped the in vitro phosphoprotein modulation by IFNα-2b and human IFNα-Le in MOLM-13 cells by IMAC/2D DIGE/MS analysis and phospho-flow cytometry, and in primary healthy and AML patient-derived PBMCs by CyTOF. In vivo, IFNα-Le and VPA efficacy were investigated in the immunodeficient NOD/Scid IL2γ−/− MOLM-13(Luc+) mouse model and the syngeneic immunocompetent BNML rat model. RESULTS: IFNα-2b and IFNα-Le differed in the modulation of phospho-proteins involved in protein folding, cell stress, cell death and p-STAT6 Y641, whereas VPA and IFNα-Le shared signaling pathways involving phosphorylation of Akt (T308), ERK1/2 (T202/T204), p38 (T180/Y182), and p53 (S15). Both IFNα compounds induced apoptosis synergistically with VPA in vitro. However, in vivo, VPA monotherapy increased survival, but no benefit was observed by IFNα-Le treatment. CyTOF analysis of primary human PBMCs indicated that lack of immune-cell activation could be a reason for the absence of response to IFNα in the animal models investigated. CONCLUSIONS: IFNα-2b and IFNα-Le showed potent and synergistic anti-leukemic effects with VPA in vitro but not in leukemic mouse and rat models in vivo. The absence of IFNα immune activation in lymphocyte subsets may potentially explain the limited in vivo anti-leukemic effect of IFNα-monotherapy in AML. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00432-019-02931-1) contains supplementary material, which is available to authorized users.